An improved machine to produce nature-identical snow in the laboratory. Issue 219 (2014) - Schleef, Stefan; Jaggi, Matthias; Löwe, Henning; Schneebeli, Martin
Abstract: We present an improved machine to produce nature-identical snow in a cold laboratory for reproducible experiments. The machine is based on the common supersaturation principle of blowing cold air over a heated water basin. The moist airstream is directed into a chamber, where it cools and the nucleation of ice crystals is promoted on stretched nylon wires. Snow crystals grow on the wires and are harvested regularly by a new automatic brush rack. Depending on the settings, different snow crystals can be produced, which are shown to be consistent with the Nakaya diagram. The main snow types are dendrites and needles. We prepared specimens from the snow produced by the snowmaker and analyzed them using microcomputer tomography. For dendrites we show that there are natural snow samples that have the same crystal shape and similar microstructural parameters, namely density and specific surface area. The machine can produce suitable amounts of snow for laboratory experiments in an efficient way. As an advantage over previous designs, uniform and reproducible snow samples can be generated under well-defined conditions.